Carbon Nanomaterials for Electrochemical Hydrogen Storage: Mechanisms and Advancements - Amir Reza Mashtizadeh; Shahab Khameneh Asl; Hossein Aghajani; Seyed Morteza Masoudpanah; Marek Wojnicki (Inorganics)
This review article investigates the rising global energy demand, which is primarily driven by population growth and industrialization, raising significant environmental concerns due to the extensive reliance on fossil fuels. In response, hydrogen is being explored as a potential eco-friendly energy solution to meet the urgent need for sustainable energy. This review covers various hydrogen storage methods, including compressed gas, cryogenic liquids, solid materials, and electrochemical techniques. Among these, electrochemical technology is highly regarded as a leading experimental approach for hydrogen storage, and it is noted for its outstanding performance under normal conditions. The characteristics of a material’s surface play a crucial role in determining its electrochemical hydrogen storage capacity. Innovative materials, such as graphene oxide and 3D graphene oxide, are particularly significant in this regard, as they can significantly enhance hydrogen storage capacity; electrochemical hydrogen storage functions by incorporating atomic hydrogen into carbon materials following the reduction of water. This article underscores the significance of green energy and the need to ensure safety and precision at room temperature and ambient pressure using electrochemical hydrogen storage techniques and mechanisms. Furthermore, it offers a comprehensive review of developments in electrochemical hydrogen storage and its mechanisms, focusing on carbon, graphene oxide, and the contributions of 3D graphene foam.